54‐1: Laser Speckle Reduction using Nanoparticle‐Embedded Liquid Crystals. Issue 1 (2nd June 2017) - Chang, Kai-Han; Shiraishi, Yukihide; Toshima, Naoki; Kobayashi, Shunsuke; Furue, Hirokazu; Chien, Liang-Chy
Abstract : The ability to reduce laser speckle of a nanoparticle‐embedded liquid crystal device with zero‐power consumption is experimentally demonstrated. The scattering profile of nanoparticles smooths out the speckles from laser. The effects from tuning nanoparticle geometry and optical characteristics of liquid crystal host are theoretically evaluated.